Polimer-zeolit Nanokompozit Gaz Ayırma Membranlarında Arayüzeyin İncelenmesi - Ağıl, Işık (Fen Bilimleri Enstitüsü, 2015)
Bu çalışmada, ticari açıdan önemli olan O2/N2, CO2/O2, CO2/N2 ve CO2/CH4 ayırma uygulamalarına yönelik membran geliştirilmesi amaçlanmış, katkılı membranlar için zeolit 4A-polivinilasetat (PVAc) sistemi seçilmiş, seçilen sistemde arafazın varlığı ve bunun membran yapısı ve ayırma özellikleri üzerine etkileri incelenmiştir. Yüksek ayırma performansına sahip membranların çok ince (<1 mm) olması ve dolayısıyla katkılı membran hazırlamada küçük zeolit tanecikleri kullanımı gerektiği için bu çalışmanın ilk aşamasında nano boyutlarda zeolit 4A sentezlenmiştir. Çalışmanın ikinci aşamasında, sentezlenen zeolit 4A kristalleri ağırlıkça %20 ve %40 katkı oranlarında PVAc polimerine katılmıştır. Yapılan saf gaz geçirgenlik ölçümlerinde, katkısız polimere kıyasla %20 nano zeolit 4A katkılı PVAc membranın O2, N2 ve CH4 geçirgenliklerinde bir miktar azalma, CO2 geçirgenliğinde ise artış gözlenmiş ve O2/N2, CO2/O2, CO2/N2 ve CO2/CH4 seçiciliklerinin de arttığı belirlenmiştir. Farklı tanecik boyutunda zeolit içeren membranlarda tanecik boyutu küçüldükçe, O2, N2 ve CH4 geçirgenliklerinde bir miktar azalma, CO2 geçirgenliğinde ise artış gözlenmiştir. Bu gözlem, zeolit 4A-PVAc sisteminde zeolitleri çevreleyen bir arafaz olduğuna işaret etmektedir. Elde edilen deneysel geçirgenlik değerlerinin, arafaz etkilerini de hesaba katan Modifiye-EOT modelinden hesaplanan etkin geçirgenlik değerleri ile uyum içerisinde olduğu görülmüştür. Zeolit 4A-PVAc sisteminde arayüzeyin varlığını Argon adsorpsiyon analizinde görülen adsorplama kapasitesindeki düşüş ve diferansiyel taramalı kalorimetre (DSC) analizleri de desteklemektedir.

This study aims to develop polymer-zeolite mixed matrix composite (MMC) membranes for important commercial gas separation applications such as the separation of O2/N2, CO2/O2, CO2/N2 and CO2/CH4 mixtures. Zeolite 4A-polyvinylacetate (PVAc) system was chosen as the polymer-zeolite system and the MMC membranes are characterized to investigate their separation properties and the zeolite-polymer interphase. Presence of an interphase surrounding small zeolite particles contributing to the effective permeability is especially important from an industrial perspective since commercial application of membranes require asymmetric membrane configuration with thin (<1 mm) selective layers, and therefore in the first part of this study, nanosize zeolite 4A was synthesized. In the second part of this study, membranes containing 20% and 40% nanosize zeolite 4A were prepared by casting-evaporation technique. Gas separation characteristics of zeolite 4A-PVAc MMC membranes indicated that 20% nano sized zeolite 4A filled MMC membranes prepared exhibited increased O2/N2, CO2/O2, CO2/N2 and CO2/CH4 selectivities and O2, N2 and CH4 permeabilities but decreased CO2 permeability when compared to the unfilled PVAc membrane. The effect of zeolite particle size in MMC membranes were also investigated, and O2, N2 and CH4 permeabilities decreased whereas CO2 permeability increased with decreasing zeolite particle size. This supports the presence of an interphase with higher resistance to gas flow in zeolit 4A-PVAc system. Furthermore, comparing the effective permeability predictions, Modified-EMT model which includes the effect of the interphase resistance was in better accordance with the experimental results obtained for the zeolite 4A-PVAc system supporting the presence of an interfacial region around the zeolite particles. The interphase effect was also observed as a reduction in the adsorption capacity of 20% zeolite 4A filled PVAc membranes. The differential scanning calorimetry (DSC) analysis results of the zeolite 4A-PVAc MMC membranes also support this observation.
Investigation Of The Interphase In Polymer-zeolite Nanocomposite Gas Separation Membranes
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2005
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2005
Keywords: Zeolit Sentezi; Gaz Ayırma; Nanokompozit Membran; Zeolite Synthesis; Gas Separation; Nanocomposite Membrane